Odpowiedzi

2009-12-14T21:40:27+01:00
X-y+1=z
2x+1/2y+3=0
z-2=0

z=2
x-y=1
2x+1/2y+3=0

z=2
y=x-1
4x+x-1+3=0 → 5x=-2 → x=-2/5

x=-2/5
y=-7/5
z=2


  • Użytkownik Zadane
2009-12-14T21:50:08+01:00
A)

x-y+1=z
2x+1/2y+3=0
z-2=0 -> z=2

x-y+1=2 -> -y=2-1-x -> y=-2+1+x -> y=x-1
2x+1/2y+3=0
podstawiając do ostatniego równania
2x+1/2*(x-1)+3=0
2x+1/2x-1/2+3=0
2,5x+2,5=0
2,5x=-2,5
x=-1
y=x-1 -> y=-1-1 -> y=-2

oraz
b).

x-y=2z -> z=(x-y)/2
x-y+3=0 ->x=y-3
3z-2x+y=0 -> z=(2x-y)/3

przyrównując równanie jeden i trzy
(x-y)/2=(2x-y)/3 /*2*3
3(x-y)=2(2x-y)
3x-3y=4x-2y /-3x+3y
0=x+y
wstawiając z równ. nr 2
0=y-3+y
-2y=-3
y=3/2
x=-y -> x=-3/2
z=(-3/2-3/2)2=(-6/2)/2=-3/2